The impact of macroeconomic variables on REIT Returns: a case of South Africa and Brazil - Zwane, Sibongile (My University, 2020)
Purpose: The paper aims to study the relationship between macroeconomic variables and the returns of REITs listed on listed on São Paulo Stock Exchange and the Johannesburg Stock Exchange in order to assess the macroeconomic risk factors through empirical findings for foreign investors over the period of January 2014 to December 2017. Methodology: The analysis will be in two parts. The first part employs a multi linear regression model and estimation using the ordinary least squares (OLS) will be used to determine the relationship between the dependent variable (the REIT Returns) to the independent variables (macroeconomic variables). The second part will make use of the ICAPM which was developed by Merton (1973) and will analyse the impact of time-varying factors such as interest rates, money supply and oil price fluctuations on REIT returns. Findings: The findings of the study showed that there is an insignificant negative relationship between interest rates and REIT returns in both South Africa and Brazil, an insignificant positive relationship between money supply and REIT returns in South Africa and Brazil. South African REIT returns showed a negative relationship with crude oil prices, however, the Brazilian REIT returns showed a more significant positive relationship with crude oil prices
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science (Building), 2020